2017
DOI: 10.20517/2347-8659.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

The association between human cytomegalovirus and glioblastomas: a review

Abstract: Human cytomegalovirus (HCMV) was reported in glioblastoma multiforme (GBM) over a decade ago and this finding has the potential to increase our understanding of the disease and it offers an alternative tumor-specific therapeutic target. Due of this promise, there is a fair amount of time, energy and money being directed towards understanding and utilizing this connection for eventual therapeutic purposes. Nevertheless, the association between GBM and HCMV remains controversial. Several studies have reported co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Risk factors for GBM include exposure to ionizing radiation [ 5 ], certain use of electronics [ 6 , 7 , 8 ], and infection by viruses such as human cytomegalovirus (HCMV) [ 9 , 10 , 11 ]. The biological mechanism of GBM remains a topic of controversy [ 12 , 13 ]. Therapy for GBM remains challenging due to the lack of efficient biomarkers and drug targets [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for GBM include exposure to ionizing radiation [ 5 ], certain use of electronics [ 6 , 7 , 8 ], and infection by viruses such as human cytomegalovirus (HCMV) [ 9 , 10 , 11 ]. The biological mechanism of GBM remains a topic of controversy [ 12 , 13 ]. Therapy for GBM remains challenging due to the lack of efficient biomarkers and drug targets [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies put extra emphasis on the indirect role of CMV in cancer (115,116). For instance, Dey et al suggested that the association between glioma and CMV is an "observational association" (117).…”
Section: Hcmv Oncomodulation and Its Significance In Tumor Microenvironmentmentioning
confidence: 99%
“…Some studies put extra emphasis on the indirect role of CMV in cancer ( 115 , 116 ). For instance, Dey et al.…”
Section: Hcmv Oncomodulation and Its Significance In Tumor Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations